OPTIMALISASI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS X MELALUI PENDEKATAN KONFLIK KOGNITIF PADA MATERI ALJABAR DI SMA NEGERI 1 BAITUSSALAM - Riki Musriandi (CV. Abid Abadi Jaya, 2025)
This study aims to optimize students’ mathematical communication skills through the implementation of a cognitive conflict approach in algebra learning for tenth-grade students at SMA Negeri 1 Baitussalam. This research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were 20 students. Data were collected through tests, observations, and field notes. The results indicated that the implementation of learning improved from an average score of 2.80 (good category) in the first cycle to 3.47 (very good category) in the second cycle. Students’ mathematical communication skills in oral form also improved, as indicated by the decrease in the low category and the increase in the good and very good categories. Furthermore, written mathematical communication skills showed significant improvement, with the average score increasing from 63.34 in the first cycle to 78.34 in the second cycle, and classical mastery improved from 30% to 80%. Therefore, the cognitive conflict approach is proven to be effective in optimizing students’ mathematical communication skills in algebra learning.